2019
DOI: 10.1515/revneuro-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Memantine for the treatment of ischemic stroke: experimental benefits and clinical lack of studies

Abstract: Stroke is an important cause of mortality and disability worldwide. Immediately after stroke onset, the ischemic cascade initiates and deleteriously affects neural cells. Time to reperfusion therapy is a critical determinant of functional recovery in stroke patients. Although recent trials have shown the significant efficacy of endovascular thrombectomy, either alone or with intravenous tissue plasminogen activator, in improving the functional outcomes of stroke patients with large vessel occlusion, hours can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Another drug, memantine, works by blocking the overstimulated NMDA receptors and preventing the neurotoxicity caused by the massive release of glutamate [ 56 ]. Few preclinical studies have shown that memantine decreases the volume of infarction in stroke patients and also improves neurological outcomes [ 56 ]. Thus it can be used as an adjunct and alternative agent to protect neuronal tissue, which has undergone ischemia [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Another drug, memantine, works by blocking the overstimulated NMDA receptors and preventing the neurotoxicity caused by the massive release of glutamate [ 56 ]. Few preclinical studies have shown that memantine decreases the volume of infarction in stroke patients and also improves neurological outcomes [ 56 ]. Thus it can be used as an adjunct and alternative agent to protect neuronal tissue, which has undergone ischemia [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…Few preclinical studies have shown that memantine decreases the volume of infarction in stroke patients and also improves neurological outcomes [ 56 ]. Thus it can be used as an adjunct and alternative agent to protect neuronal tissue, which has undergone ischemia [ 56 ]. So in a way, it can provide a window to minimize the brain damage until reperfusion therapy for stroke can be initiated [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…Cholinesterase inhibitors (donepezil, galantamine, rivastigmine, and physostigmine), 49 , 50 , 51 N ‐methyl‐D‐aspartate (NMDA) receptor antagonists (memantine), 50 , 51 nerve repair and brain‐stimulating medications, and nootropic medications, such as piracetam, butylphthalide, ergoline, nimodipine, citicoline, Ginkgo biloba, and some proprietary Chinese medicines.…”
Section: Treatment Of Psamentioning
confidence: 99%
“…Extracellular release of glutamate in large amounts causes excessive activation of NMDA receptors after acute cerebral ischemia. 50 , 61 , 62 , 63 , 64 , 65 This triggers the activity of pathological molecules and a cascade effect, leading to cell death. As a reversible NMDA receptor antagonist, memantine blocks the excessive activation of neurons by glutamate.…”
Section: Clinical Study and The Mechanism Of Action Of Therapy On The Treatment Of Psamentioning
confidence: 99%
“…Memantine may confer neuroprotection through more potent inhibition of extrasynaptic NMDA receptors (Zhao et al, 2006; Léveillé et al, 2008; Okamoto et al, 2009; Milnerwood et al, 2010; Xia et al, 2010) without significantly affecting physiologic glutamatergic transmission. In addition, this drug has few undesirable drug interactions or adverse effects and is a well-tolerated medication for neurological disorders (Seyedsaadat and Kallmes, 2019). Several studies have investigated the effects of memantine on neurons, and the drug is known to increase the release of glial cell neurotrophic factors, contributing to neuronal survival (Wu et al, 2009).…”
Section: Therapeutic Interventionsmentioning
confidence: 99%